Despedida - Alves, Andressa Soares Castro (Universidade Federal de São Carlos, 2020)
The present work is intended to conclude the Bachelor's Degree in Medicine at the Federal University of São Carlos. It is about the student's trajectory and her reflections on the period
Farewell
Keywords: Narrativa; CIENCIAS HUMANAS::EDUCACAO::ORIENTACAO E ACONSELHAMENTO::ORIENTACAO EDUCACIONAL